Neo-Daoism - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2008)
Neo-Daoism has often been approached from a historical perspective. Toward the end of the Han dynasty, a major political protest movement known as qing-yi (清議) or ‘Pure Criticism’ shook the Chinese world. Led by eminent scholar-officials and students of the imperial academy, it was directed especially against the alleged abuses of powerful palace eunuchs. The movement, however, was ruthlessly suppressed. Consequently, many literati seem to have become disillusioned with the political process. This not only marked a turning point in Han politics but also impacted with considerable force on the course of culture and philosophy. The Wei dynasty (220-65) formally ended the rule of the Han in 220 CE. Politics remained extremely volatile. Externally, two rival regimes challenged the Wei claim to supremacy; internally, power struggles among factions of the ruling elite rendered life at court doubly treacherous. In this context, we find the appearance of an influential upper-class cultural phenomenon known as ‘Pure Conversation’ (qing-tan 清 談), in which scholar-officials and men of letters in general gathered for pleasure and devoted their intellectual and creative energies to music, poetry, philosophy, and other forms of cultured discourse. Xuan-xue in the general sense outlined above formed a major topic of Pure Conversation. In view of the turbulent political background, some scholars have concluded that Neo-Daoism contained a strong element of escapism. According to this interpretation, whereas qing-yi centered on political criticism, qing-tan, its cultural successor, was self-consciously non-political. Fearing for their safety and disheartened by the apparent futility of political engagement in effecting meaningful change, the literati turned their attention to, as it were, purer pursuits. Although the political background is important, this does not give the whole picture. Certainly, to some scholars at that time politics was so corrupt as to make a mockery of any sense of honor and moral integrity, but many continued to harbor hope in revitalizing the rule of Dao. Neo-Daoism is complex and encompasses a range of responses to new demands and challenges that came to shape the intellectual landscape of post-Han China.